Influence of binder float length on the out-of-plane and axial impact performance of 3D woven composites. (August 2021) - Ralph, Calvin; Dahale, Monali; Neale, Geoffrey; Ramaswamy, Karthik; McCarthy, Michael; Yoo, Sanghyun; Toso, Nathalie; Kelly, John; McGarrigle, Cormac; Archer, Edward; Harkin-Jones, Eileen; McIlhagger, Alistair
Highlights: Energy absorption decreases as binder float length increases for out-of-plane impact. Damage tolerance of layer-to-layer composites increases with binder float length. Longer float lengths display a higher crush force efficiency during axial crushing. Longer float lengths results in reduced transverse and axial cracking for in-plane. Abstract: This paper shows modifying binder float-length, an easily adjustable parameter, there is significant influence on impact energy absorption, impact resistance and damage tolerance in 3D-woven layer-to-layer carbon/epoxy composites. Binder float-length was changed by modifying textile design without changing loom set-up. Three float lengths (1/2, 2/2 and 3/2) in consistent architecture were woven using constant warp density. Out-of-plane drop-weight impact was performed at 32 J&42 J energy and showed increases in float-length decreased energy absorption by 49% and 32% respectively in warp direction with no significant changes in weft. Conversely, in axial impact tests, higher float length showed higher crush force efficiency and specific energy absorption. This study has also concluded, in both out-of-plane and axial impact scenarios, higher float lengths increase damage tolerance. This work has expanded how minor changes in preform parameters can significantly change both out-of-plane and in-plane impact performance of 3D-woven composites without increased manufacturing cost, time or complexity.